Boiler incidents in process industry sequence analysis / Liyana Ahmad Shuib - Ahmad Shuib, Liyana (2018)
This paper presents a quantitative risk assessment-based approach for assessing and evaluating the plant safety involving boiler failure in process industry. Lists of contributory and sub-contributory factors of boiler failure incidents are developed. These factors are grouped under more general categories; Human Error (HE), Management Error (ME), Equipment Error (EE) and Design Error (DE). Boiler failure incident sequences are developed using Event Trees (ET). A combination model of Event Trees and Fault Trees are developed and has been applied to Loy-Lange Box Company Boiler Explosion Incident for validation of resulting model. From the calculation, it can be seen that the percentage for a boiler failure incident to occur in process industry is 0.187% while the percentage for the boiler to stay at safe condition is about 50%. This shows how important it is to improve the efficiency of prevention barrier in order to keep the boiler under safe and good condition.